Dietary total antioxidant capacity and colorectal cancer: A large case–control study in Italy. Issue 6 (4th April 2013) - La, Carlo; Decarli, Adriano; Serafini, Mauro; Parpinel, Maria; Bellocco, Rino; Galeone, Carlotta; Bosetti, Cristina; Zucchetto, Antonella; Polesel, Jerry; Lagiou, Pagona; Negri, Eva; Rossi, Marta
<x xml:space="preserve">Abstract</x> A favorable role of fruit and vegetables on colorectal cancer risk has been related to the antioxidant properties of their components. We used data from an Italian case–control study including 1, 953 patients with incident, histologically confirmed colorectal cancer (1, 225 colon and 728 rectal cancers). Controls were 4, 154 patients admitted to hospital for acute, non‐neoplastic conditions. A reproducible and valid food frequency questionnaire was used to assess subjects' usual diet. Total antioxidant capacity (TAC) was measured using Italian food composition tables in terms of ferric reducing‐antioxidant power (FRAP), Trolox equivalent antioxidant capacity (TEAC) and total radical‐trapping antioxidant parameter (TRAP). We estimated the odds ratios (ORs) and the corresponding 95% confidence intervals (CIs) through multiple logistic regression models, including terms for potential confounding factors, and energy intake. TAC was inversely related with colorectal cancer risk: the OR for the highest versus the lowest quintile was 0.68 (95% CI, 0.57–0.82) for FRAP, 0.69 (95% CI, 0.57–0.83) for TEAC and 0.69 (95% CI, 0.57–0.83) for TRAP. Corresponding values, excluding TAC deriving from coffee, were 0.75 (95% CI, 0.61–0.93) for FRAP, 0.76 (95% CI, 0.61–0.93) for TEAC and 0.71 (95% CI, 0.57–0.89) for TRAP. The inverse association was apparently—though not significantly—stronger for rectal than for colon cancer. This is the first case–control study indicating consistent inverse relations between dietary TAC and colorectal cancer risk.